Educação sexual emancipatória e os desafios contemporâneos: um ensaio teórico sobre o relatório das ofensivas antigênero - Donzeli, Taina Vieira [UNESP] (2025)
This dissertation aims to investigate how anti-gender offensives impact the development and practice of emancipatory sex education in contemporary times. It is based on the report "Anti Gender-Offensives in Brazil: State policies, legislation and social mobilization" (2021). This document, prepared by several civil society organizations, took stock of the anti-gender offensives in Brazil between 2019 and 2021. It addresses the importance of emancipatory sex education as a tool to promote gender equality, respect for diversity, and the breaking of stigma and prejudice. In this research, the strategies of censorship and exclusion were analyzed, as well as the influence of neoconservatism on the development of public policies. We also examined the consequences of anti-gender offensives for guaranteeing the rights of women and LGBTQIAPN+ groups. The objective of this research was to analyze the impacts of anti-gender offensives on the possibility of promoting an emancipatory sexual education. In the methodology adopted, through categorization, it was sought to delimit and discuss how the offensive anti-gender influence in three specific areas: restriction of critical training of students, perpetuation of discrimination and exclusion, censorship of debates about gender and sexuality contributing to disinformation.